Siberia: beautiful, bleak, full of uncertainty - Rolston, Holmes, 1932-2025, author; Fort Collins Coloradoan, publisher (Colorado State University. Libraries, 1997)
Report on a trip to Siberia and Lake Baikal, with a focus on conservation biology, led by Russian scientists, and sponsored by the American Association for the Advancement of Science. Riding the Trans-Siberian railway across its wildest stretches and exploring the oldest and deepest lake on Earth, with 1,500 endemic species. What should Siberia be? Forever wild? Developed? Certainly, not further exploited and impoverished.
Keywords: Lake Baikal; conservation biology; Siberia